Effects of labor induction in obesity with delayed pregnancy: A retrospective study based on Chinese obese primipara - Liu, Shuhua; Song, Bing; Liu, Dehong; Zheng, Chenmin; Wu, Xiumei; Wei, Zhaolian; Chen, Xianxia (Frontiers in Endocrinology, 2023)
Objective To test the hypothesis that obese primiparous women with an unfavorable cervix in delayed pregnancy may experience a worse induction of labor. Study design In total, 467 primiparas with poor cervical condition and delayed pregnancy (gestational age [GA]: >40weeks) were divided into an obese primiparas group (body mass index [BMI] >30kg/m2; n=166) and a non-obese primiparas group (BMI < 30kg/m2; (n=301). Labor was induced by various methods, double balloon, dinoprostone inserts, and amniotomy combined with oxytocin depending on the Bishop score. Experimental data were analyzed by Statistical Product Service Solutions (SPSS). Results BMI in the obese primiparas group was higher than in the non-obese group (33.91 ± 2.67 versus 24.09 ± 5.78, p<0.001), and there were significant differences in uterine tone and duration of contractions between the two groups in the second stage of labour (p=0.041, p=0.026, respectively).The rate of cesarean section (CS) was significantly higher in the primiparas group (23.49% versus 12.29%; P=0.002). There was a significant difference between the two groups in terms of the duration of time to vaginal delivery (VD) (18h versus 8h; P <0.001) while the duration until VD in the obese primiparas group within 12 hours and 24 hours was significantly longer (P <0.001). After adjusting for possible confounders, caesarean section rates remained high in the obese primiparas women (OR: 2.564;95%CI1.919,3.864;P<0.001). Similarly, after adjusting for the same confounding factors, obese primiparas women increased the duration until VD within 24 h by 3.598 hours. Conclusion Obese primiparas with an unfavorable cervix in delayed pregnancy have a significantly higher risk of CS and a longer duration until VD than non-obese primiparas during labor induction.